Nationalism in Chinese Language Textbooks for Primary Schools in Pre-Independence Malaya (1904-1957) - Chang, Lan Chin (2011)
Prior to the period of World War II, nationalism of the overseas Chinese in Malaya was closely related to the history of modern China. This was proved by historical records and research. It can also be seen from the publication of Chinese textbooks. During pre-World War II and beginning years after World War II, Chinese schools adopted textbooks imported from mainland China. Textbooks were promoted the strong spirit of anti-imperialism and anti-colonialism, reflecting a strong sense of Chinese nationalism. In 1951, the colonial government in Malaya accepted recommendations from the Fenn-Wu Report and set up a Chinese School Textbook Revision Committee to adapt Chinese school textbooks. Textbooks were revised to invoke local awareness through the portrayal of a Malayan orientation. Since then, a new era started in Malaya, with textbooks containing local identity. From beginning of the 20th century to early years after World War II, was the period of Chinese in mainland China seeking self-preservation and self-strengthening to the nation. How did nationalism appear in Chinese schools’ textbooks in Malaya? Did it change from time to time ? What was its relations with historical processes? This study will analyse and probe the above mentioned questions through the Chinese Language textbooks. This study focuses on Chinese Language textbooks used by Chinese primary schools in Malaya between 1904 to 1957. It attempts to examine the ideological content of the textbooks, to determine the types of nationalism that emerged and its changes, as well as its relations with historical processes. The thesis consists of six chapters. Chapter 1 is the introduction. Chapter 2 provides an overview of the development of new-type Chinese education in Malaya. This is necessary as background knowledge in the discussion at the later part. The subsequent three chapters form the core of this study, examining the emergence of nationalism in Chinese Language textbooks during the period of the late Qing dynasty, till the Republic of China and before the independence of Malaya. Chapter 6 is the conclusion. This study concludes that from the first decade of the 20th century to the mid 20th century, the ideological contents which are embodied in Malayan Chinese Language textbooks are closely related to the historical development. It reflects the changes of the orientation of national identity as well as the cultural identity of Chinese in Malaya which have changed from China-centred to Malaya-orientated. To a certain extent, it could be perceived as microcosm as well as the process of shaping of Malayan Chinese ethno-nationalism. Key words: Chinese Language, textbooks, nationalism, Malaya, pre-independence